Lavender (Lavandula angustifolia) Essential Oil for Pain Management in Parturient Women During the First Stage of Labor - Pratiwi, Lusy (HM Publisher, 2024)
Labor pain is an unavoidable part of childbirth, often causing significant distress and anxiety in parturient women. While pharmacological pain management options exist, there is growing interest in non-pharmacological alternatives, such as aromatherapy, due to their potential to provide relief with minimal side effects. Lavender essential oil, in particular, has been recognized for its calming and analgesic properties. This study aimed to investigate the effectiveness of lavender essential oil aromatherapy in reducing pain intensity during the first stage of labor. A randomized controlled trial was conducted, involving 100 participant women experiencing their first stage of labor. Participants were randomly assigned to either the intervention group (n=50), receiving lavender essential oil aromatherapy, or the control group (n=50), receiving a placebo aromatherapy. Pain intensity was assessed using the visual analog scale (VAS) before and after the intervention. The results demonstrated a statistically significant reduction in pain intensity in the intervention group compared to the control group (p < 0.05). The mean VAS score decreased from 7.2 ± 1.5 to 4.3 ± 1.2 in the intervention group, while the control group showed a decrease from 7.0 ± 1.6 to 6.2 ± 1.4. In conclusion, lavender essential oil aromatherapy appears to be an effective non-pharmacological method for reducing pain intensity during the first stage of labor. The findings suggest that it can be a valuable addition to the pain management strategies offered to women during childbirth.